Learning for the Future beyond COVID-19: A Critical Alternative to the Neoliberal Model of Development - David Neilson (Societies, 2022)
This paper reviews how COVID-19 became a global pandemic, why we now have to live with it, and what needs to be done to stop viruses going global in the future. Specifically, it argues that the still prevailing neoliberal model of development combined with related forms of class structure and ideological struggle all but guaranteed that the priorities of global capital and its agents, along with COVID-19, would win out in the end. Vaccinations have become the only path for resolving the tension between neoliberal capitalism and COVID-19 suppression. However, they take time to develop, are hampered by the capitalist model of vaccine production and distribution, and face a resistant alienated precariat. As a critical alternative, this article explores the neoliberal model of development’s democratic socialist transformation with particular reference to the prevention of global pandemics.